A novel damped braced tube system for tall buildings in high seismic zones. (16th February 2022) - Ishibashi, Yoji; Terazawa, Yuki; Tanaka, Haruki; Yokoyama, Ryo; Mizuno, Hiroki; Takeuchi, Toru
Summary: The damped outrigger system is known to efficiently provide additional damping in buildings with heights of over 250 m. However, particularly for supertall buildings in the center of Tokyo, Japan, the outrigger truss from the center core to the exterior columns need to span distances of more than 20 m. This increases the flexural stiffness demand on the outrigger that leads to larger truss depths making the damped outrigger system inefficient. For such tall buildings with large plans, a new damping modification system, the "damped braced tube system" is proposed, where the exterior surface of the elastic mega braces are partially removed vertically to create a split and are replaced with dissipaters (energy‐dissipation devices). The damped braced tube system enhances the seismic performance as the exterior surfaces of the elastic mega braces work together with the damped slits like in a coupled wall system and increases the overall damping ratio. In this paper, numerical models were constructed based on a real project in Japan consisting of a 397‐m supertall building employing the damped tubular braced system using oil dampers (referred to as viscous dissipaters). A series of generalized response spectrum based numerical analyses and optimizations were performed to minimize the seismic response. The proposed system exhibited improved damping performance with the first to third mode damping ratios reaching to more than 7% while providing a wide range of options for dissipater distribution for design. Finally, the elevation of the slit's base is recommended to be equal to 0.22 of the total building height considering the trade‐off relationship between the first modal damping ratio and the fundamental period.